AN NEW IOT SECURITY DEVICE FOR WOMAN SAFETY - A.Selvi; S.Thilagamani (International Journal of Psychosocial Rehabilitation, 2020)
In genuine world, women are relaxation and have numerous issues identifying with their security reason. They have to persevere through various irritating things and need to demonstrate government has given wellbeing through control and guideline to society. Despite the fact that there are a few genuine frameworks for security purposes need of new great wellbeing framework is broad. In order to beat such issues great wellbeing framework for women is required. This paper depicts in regards to verify partner degree verified electronic framework for women that contain Arduino controller and distinguished like rectifier, help convertor, pulse gadget, MEMS. A caution, Crystal dial, GPS, and electric stun are utilized right now. At the point when the women are in damage, the gadgets sense the figure structure like heartbeat rate, alteration in condition. When the contraption gets work it discover the situation of the sufferer by the heading discoverer. By misuse, the sufferer’s position is sent to the vault contact assortment. In the event that the lady is assaulted by the person in question, at that point she quickly presses the catch and it will create a current. At the point when the flow delivers the injured individual will get a stun on contacting the lady.